Analysis of Dynamic Characteristics of Hydraulic Driven System for Weight Bearing Lower Limb Exoskeleton. Issue 1 (1st November 2022) - Su, QiYing; Pei, ZhongCai; Tang, ZhiYong
Abstract: A new kind of weight-bearing lower limb exoskeleton driven by hydraulic cylinder is designed, and its structural characteristics and driving principle are analysed. The mathematical model and control block diagram of the valve controlled unsymmetrical cylinder system for the controlled rotary joint are established. The effects of structural parameters such as servo valve bandwidth, load mass and hydraulic cylinder size on the dynamic characteristics of the system are studied, and the force tracking curve optimized by structural parameters is given to prove the correctness of the theoretical analysis of the system, which provides theoretical support for the design of the weight-bearing lower limb exoskeleton.